Optimization of operating parameters of seeding device in plot drill with seeding control system - Cheng, Xiupei; Li, Hongwen; He, Jin; Wang, Qingjie; Lu, Caiyun; Wang, Yingbo; Wang, Chao; Wang, Chunlei; Lou, Shangyi (International Journal of Agricultural and Biological Engineering, 2021)
Plot drill has a significant impact on field breeding by replacing manual seeding. However, the seeding performance of plot drill needs to be further improved as the mechanical transmission method cannot work under the optimal combination of operating parameters. In this study, a cone compartment tray of sowing device was evaluated under the laboratory conditions, using a self-designed seeding control system to adjust the operating parameters. Among them, a plot seeding control system was involved that could set operating parameters through an Android terminal, which effectively reduced the difficulty of parameters adjustment. The method of central composite experiment design was employed to conduct experiments and explore the effects of experiment factors such as lifting height of storage tube (LHST), rotation speed of cone compartment tray (RSCCT), and rotation speed seed distributor (RSSD) on the seeding uniformity coefficient of variation among rows (SUCVR) and the rate of damaged seeds (RDS). For SUCVR of wheat, the results showed that the importance order of main factors from high to low was RSSD, RSCCT and LHST. And for SUCVR of buckwheat, RSCCT had the largest influence, followed by RSSD, and LHST had the smallest influence. For RDS of wheat and buckwheat, only RSSD had a very significant effect among the main factors. The experiments data of wheat indicated that when operated at 27.2 mm for LHST, 4.5 r/min for RSCCT and 1169 r/min for RSSD, the sowing performance of wheat was optimal, with SUCVR and RDS values of 5.02% and 0.117%, respectively. The buckwheat seeding performance was found to be optimal when the LHST, RSCCT and RSSD were 26.5 mm, 3.9 r/min and 711 r/min, and SUCVR and RDS were 4.74% and 0.113%. The seeding control system realized the electromechanical control of the seeding equipment, was convenient for parameter setting and stepless adjustment, and could be operated under an optimized combination of operating parameters. The research results could provide a reference for the performance improvement and application of plot drill.Keywords: plot drill, seeding device, seeding control system, seeding performance, parameter optimizationDOI: 10.25165/j.ijabe.20211403.6218Citation: Cheng X P, Li H W, He J, Wang Q J, Lu C Y, Wang Y B, et al. Optimization of operating parameters of seeding device in plot drill with seeding control system. Int J Agric & Biol Eng, 2021; 14(3): 83–91.